Optimizing Civil Procedural Law in Environmental Cases Related to Peatland Burning: Legal Approaches for Sustainable Peatland Management - Hamdi Hamdi; Agus Sugiarto; Mahatidanar Hidayat (APPTHI, 2023)
Abstract. Burning peatland has serious implications for the environment, and legal efforts are crucial in addressing this issue. However, the dimension of civil procedural law applied in environmental cases in Indonesia, especially those related to peatland burning, has not fully supported recovery efforts aligned with sustainable development goals. This research explores the dimension of civil procedural law in the context of handling environmental cases, particularly those related to peatland burning. The primary focus of this study is on the stages of civil procedural law involving initial examination, the examination process in terms of evidence presentation, the judge’s decision, and decision enforcement or execution. This research recommends optimizing the application of civil procedural law by developing policies in the examination stages. Improving regulations and guidelines in the evidence presentation stage can be a solution to overcome these challenges, allowing judges to make more accurate decisions based on relevant facts and evidence. In dealing with unpredictable risks, especially those related to industrial activities, this research also advocates for reconsideration of the fault-based liability doctrine. Additionally, the study identifies the need to consider more absolute strict liability in the environmental context. This principle can be adopted to address peatland burners by applying liability without fault. Optimization efforts in the examination stage, consideration of the liability doctrine, and the application of the principle of strict liability are expected to enhance the effectiveness of the legal handling of environmental cases, achieve better recovery, and support sustainable development goals. Abstrak. Pembakaran lahan gambut memiliki dampak serius bagi lingkungan, dan upaya hukum sangat penting dalam menangani masalah ini. Namun, dimensi hukum acara perdata yang diterapkan dalam kasus lingkungan, khususnya yang terkait dengan pembakaran lahan gambut, belum sepenuhnya mendukung upaya pemulihan yang sejalan dengan tujuan pembangunan berkelanjutan. Penelitian ini mengeksplorasi dimensi hukum acara perdata dalam konteks penanganan kasus lingkungan, terutama yang terkait dengan pembakaran lahan gambut. Fokus utama dari studi ini adalah pada tahapan hukum acara perdata yang melibatkan pemeriksaan awal, proses pemeriksaan (penyajian bukti), keputusan hakim, dan pelaksanaan keputusan (eksekusi). Penelitian ini merekomendasikan optimalisasi penerapan hukum acara perdata dengan mengembangkan kebijakan pada tahap pemeriksaan. Peningkatan regulasi dan pedoman dalam tahap penyajian bukti dapat menjadi solusi untuk mengatasi tantangan ini, memungkinkan hakim membuat keputusan yang lebih akurat berdasarkan fakta dan bukti yang relevan. Dalam menghadapi risiko yang tidak dapat diprediksi, khususnya terkait dengan kegiatan industri, penelitian ini juga mendukung untuk mempertimbangkan kembali doktrin tanggung jawab berdasarkan kesalahan. Selain itu, studi ini mengidentifikasi kebutuhan untuk mempertimbangkan tanggung jawab mutlak yang lebih besar dalam konteks lingkungan. Prinsip ini dapat diadopsi untuk menangani pembakar lahan gambut dengan menerapkan tanggung jawab tanpa kesalahan. Upaya optimalisasi pada tahap pemeriksaan, pertimbangan doktrin tanggung jawab, dan penerapan prinsip tanggung jawab mutlak diharapkan dapat meningkatkan efektivitas penanganan hukum kasus lingkungan, mencapai pemulihan yang lebih baik, dan mendukung tujuan pembangunan berkelanjutan. Kata kunci: Pembakaran lahan gambut, Hukum acara perdata, Kasus lingkungan hidup, Pembangunan berkelanjutan, Liability without fault